The Analysis of Lobster Production and Resource Management in West Java Province, Indonesian Fisheries Management Area (IFMA) 573 - Efrillia Nabila fauzy; Bintang Sanjari; Bima Prayasa Adisati; Septrinawati; Ahmad Maulana Malik; David N. Ogbonna; Sudirman Adibrata (Coastal and Marine Journal, 2025)
Lobster is a high-value fishery commodity in the southern coastal waters of West Java, which are included in WPPNRI 573. Increasing market demand has led to higher lobster fishing activities, potentially threatening the sustainability of lobster resources. This study aims to analyze lobster production in West Java from 2019–2024, identify the dominant lobster species, examine the factors influencing lobster exploitation, formulate sustainable lobster management strategies, and analyze government efforts to support sustainable lobster resource management in WPPNRI 573. The study was conducted from April to May 2025 using data obtained from the Ministry of Marine Affairs and Fisheries. A literature review method with a qualitative descriptive approach was employed, drawing on lobster production data and relevant scientific literature to analyze trends and related issues in lobster fisheries. The results showed that lobster production in West Java fluctuated, with the highest production recorded in 2020 at 167.36 tons and the lowest in 2023 at 24.42 tons. The dominant lobster species found were sand lobster (Panulirus homarus), pearl lobster (Panulirus ornatus), and bamboo lobster (Panulirus versicolor). The high fishing activity has caused lobster utilization to reach a fully exploited status, requiring sustainable management through minimum catch size regulations, fishing effort control, stock monitoring, the use of environmentally friendly fishing gear, supervision of illegal fishing, and lobster aquaculture development to ensure the sustainability of lobster resources.